Temporal and spatial variations in the structure of the rocky reef fish community of the southwest Gulf of California, Mexico - H Pérez-España; F Galván-Magaña; LA Abitia-Cárdenas (Ciencias Marinas, 1996)
Many rocky reefs exist in the Gulf of California; however, there are few studies on the fish communities that inhabit them. In the present work, these communities are evaluated through visual censuses at four sites of the southwestem coast of the gulf. The specifíc richness, frequency, evenness and diversity were analyzed at each site. Seasonal changes and differences among the sites studied were also analyzed. A total of 76 species was registered. Five species were the most abundant in most of the zones and during the greater part of the study: Stegastes spp., Thalassoma lucasanum, Abudefduf troschelii, Chromis atrilobata and Haemulon maculicauda. Only the first three species were present in all censuses made. Differences were found in the structure of the communities between different seasons and between study sites; however, the diversity values had no significant differences. The zone with the greatest number of species was Cueva de León. A positive relationship was found between specific richness and temperature.